Molecular characterization of grapevine from Santa Catarina, Brazil, using microsatellite markers - Schuck, Mariane Ruzza; Moreira, Flávia Maria; Guerra, Miguel Pedro; Voltolini, José Afonso; Grando, Maria Stella; Silva, Aparecido Lima da (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to characterize the grape germplasm in Santa Catarina, Brazil, using microsatellite DNA markers (simple sequence repeats – SSR). The DNA samples were collected from leaves and shoots of accessions of public and private collections from the counties Urussanga, Nova Trento, Rodeio, São Joaquim, Campos Novos, Videira, and Água Doce. Ten SSR loci (VVS2, VVMD5, VVMD7, VVMD27, VrZAG62, VrZAG79, VVMD25, VVMD28, VVMD31, and VVMD32) were analysed by capillary electrophoresis. Molecular profiling was conducted for 190 grapevines (European, American, and hybrids), and 67 genotypes were obtained. The data were compared with each other and with those from the literature and from online databases, in order to identify varieties and discover cases of synonymy and homonymy. Forty molecular profiles corresponded to known varieties, while 27 genotypes were described for the first time. The existence of typical germplasm composed mainly of American and hybrid varieties is an important finding for local viticulture. Applications of the results rely on quality control and certification at the nursery level. Increasing precision in the characterization of grapevine genotypes may help breeding programs.